Characterization and potential of plant growth promoting rhizobacteria isolated from native Andean crops - Ogata-Gutiérrez, Katty (2017)
Bacteria isolated from soil and rhizosphere samples collected in Peru from Andean crops were tested in vitro and in vivo to determine their potential as plant growth promoters and their ability to induce systemic resistance to Alternaria alternata in tomato plants. The isolates were identified by sequencing their 16S ribosomal RNA gene. Test for phosphate solubilization, and indolacetic acid were also carried out, together with in vitro antagonism assays in dual cultures towards the plant pathogens Fusarium solani, A. alternata and Curvularia lunata. The three most promising isolates (Pa15, Ps155, Ps168) belonged to the genus Pseudomonas. Further assays were carried out with tomato plants to assess their plant protection effect towards A. alternata and as growth promoters. Inoculation of tomato seeds with all isolates significantly enhanced seed germination, plantlets emergence and plant development. Bacterial inoculation also reduce damage level caused by A. alternata. The expression levels of three tomato genes involved in the jasmonate (AOS), ethylene responsive (ERF-2) and pathogenesis related (PR-P2) pathways were determined in plants challenged with A. alternata, alone or with each bacterial isolate, respectively. Results showed that at 24 h after infection, in absence of the pathogen, the expression level of the tested genes was very low. The presence of A. alternata alone and in combination with bacteria increased the transcripts of all genes. Data showed a potential of best performing isolate Ps168 to sustain tomato plants nutrition and activate defense-related genes for protection by pathogenic fungi.